Cluster-based routing protocol using traffic information. (2018) - Toulni, Hamza; Nsiri, Benayad
In recent years, VANET has gained much attention from researchers and the different actors in the field of transport, because of its crucial role in intervehicular communication and road safety. However, VANET still faces many challenges in terms of implementation. Furthermore, the routing in VANET is the most critical issue, because of its major role in the communication between vehicles. So the routing strategy must consider the periodic change in the topology and other characteristics of VANET. Moreover, the method adopted in the routing must provide the best flow of data in view of various performance metrics. In this paper, we propose a cluster-based routing protocol using the road traffic information to ensure the packet transmission in the most reliable manner and in record time. The proposal routing protocol is simulated in city environment, and the experimental result show that our protocol is very effective.